Evaluation of the Stress Grading System of Medium Voltage Motors Fed by Adjustable Speed Drives Under Elevated Ambient Temperatures - Arabul, F. Keskin; Arabul, A. Y.; Naeini, A.; Jayaram, S.; Cherney, E. (IEEE, 2023)
Today's stress grading system (SGS) used in medium voltage and high voltage motors is a combination of SiC based stress grading tape (SGT) and conductive armor tape (CAT). SGS, also identified as the corona protection system, has been developed to have good field grading properties and low temperature rise at operations under normal power frequency voltages. However, a converter voltage containing pulses with short rise time and high repetition frequency will affect the temperature distribution along the SGS. The available length and thickness of CAT and SGT, conductivity of CAT, conductivity/nonlinearity of SGT, are parameters that can be adjusted for effective stress grading systems. This paper presents an optimization strategy for the CAT length to reduce temperature rise along the end winding region for motors operating in elevated ambient temperatures.
Keywords: Engineering; Materials Science; Physics